Dampak Transformasi Digital terhadap Daya Saing Organisasi di Era Ekonomi Berbasis AI : studi pada PT Telkom Indonesia Tbk - Maatuil, TRexy Andalangi; Jonathan Saerang; Trivan Kesek; Ivan J. Tatulus; Marsyanda L. Pasuma (Indonesia Economic Journal, 2025)
This study analyzes the contribution of digital transformation to strengthening the competitiveness of PT Telkom Indonesia in a technology-driven and artificial intelligence (AI)-based economy. Using a descriptive qualitative approach through literature review and case study analysis of corporate documents, this research examines the role of digital technology integration, organizational restructuring, and the development of digital capabilities. The findings show that Telkom’s digital strategy is reinforced through the adoption of big data analytics, automation, AI-based decision-making, and the development of digital infrastructure such as data centers and cloud services. From the Resource-Based View (RBV) perspective, Telkom’s digital capabilities serve as strategic resources that drive long-term competitive advantage. Through the dynamic capability framework, Telkom also demonstrates adaptive capacity in identifying technological opportunities, developing digital services, and reconfiguring resources in response to industry dynamics. This study concludes that digital transformation significantly contributes to improving operational efficiency, service innovation, and organizational agility, thereby strengthening Telkom’s competitive position in the digitalized telecommunications industry.